Legal responsibility for crimes: regarding the specific division of offenses - Petkov, V.; Petkov, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The external aggression of totalitarian anti-democratic states against Ukraine is, among other things, caused by internal factors, including the crisis of democratic institutions and, above all, the conflicts that existed in the soviet system of law and have been recapitulated in the law of postsoviet countries. Ukraine's example of societal transformation is perhaps the most striking, as the imperial nature of power in the form of corruption, authoritarianism, repression, and disregard for rights and freedoms has also affected the newly formed Ukrainian political and economic environment. The military sphere, and especially the institution of legal responsibility of the military, is no exception, as it is extremely corruption- and crime-prone due to its isolation, conservatism, and multivector risks associated with both personal characteristics and the environment itself. Therefore, it requires urgent reform in accordance with NATO standards. However, this cannot be done without reforming the entire system of Ukrainian legislation. In accordance with the postulates of jurisprudence and practical necessity, the article substantiates the need to ensure legal certainty in the use of the terms "crime", "administrative offense", "disciplinary offense" in Ukrainian legislation, which are basic for the institution of legal liability. The authorprovides arguments in favor of distinguishing between the subject matter and grounds of liability for a crime, liability for an administrative offense and liability for a disciplinary offense in accordance with the Constitution of Ukraine. Proposals are made to create codified regulations governing various spheres of social and economic life and, above all, the military sphere.
Keywords: law and order, crime, administrative offense, disciplinary offense, legal responsibility, responsibility for an administrative offense, responsibility for a disciplinary offense